Unlocking the Potentials of Exosomes in Achilles Tendinitis - Naveen Jeyaraman; Madhan Jeyaraman; Swaminathan Ramasubramanian; Sangeetha Balaji; Sathish Muthu (Journal of Foot and Ankle Surgery (Asia Pacific))
Achilles tendinitis, a prevalent condition among athletes, is marked by inflammation and degeneration of the Achilles tendon due to factors such as overuse and mechanical overload. Current treatments are often limited in efficacy, prompting the exploration of novel therapeutic approaches. Exosomes, small extracellular vesicles released from cells, have emerged as promising agents for tendon healing due to their ability to transfer bioactive molecules and modulate cellular processes. This review examines the role of exosomes in the treatment of Achilles tendinitis, highlighting their anti-inflammatory, regenerative, and immunomodulatory properties. Exosomes derived from mesenchymal stem cells (MSCs) and tendon stem cells (TSCs) can reduce inflammation by modulating cytokine levels and suppressing proinflammatory pathways. They promote tenocyte proliferation, enhance extracellular matrix (ECM) synthesis, and improve tendon structure and function. Preclinical studies demonstrate significant benefits of exosome therapy, including reduced inflammation, improved collagen organization, and enhanced biomechanical properties of the tendon. Early clinical trials indicate that exosome-based therapies are safe and potentially effective, showing promise in reducing pain and improving tendon function. However, challenges such as standardizing exosome isolation and characterization, navigating regulatory pathways, and understanding long-term safety and efficacy must be addressed. Future research should focus on optimizing exosome sources, dosages, delivery methods, and exploring combination therapies to enhance therapeutic outcomes. Exosomes could revolutionize the management of Achilles tendinitis, offering a novel and effective treatment modality.